The Influence of Service Quality, Store Atmosphere, and Location on Customer Satisfaction Case Study on Seblak Prasmanan Ndaa - Murniasari, Refi; Kusumaningtyas, Dian (Universitas Nusantara PGRI Kediri, 2025)
Research aim: This study aims to find out whether the influence of service quality, store atmosphere, and location affects customer satisfaction in the buffet seblak ndaa Design/Methode/Approach: this study uses quantitative method research. The population of all customers who visited the ndaa buffet seblak is unknown. A sample of 100 respondents was taken using the probability sampling technique with the random sampling method. Instrument testing with validity tests and reliability tests. Meanwhile, data analysis techniques with classical assumption test techniques, multiple linear regression analysis, hypothesis tests with SPSS version 25 application. Reseach Finding : This study produced the results that in the first hypothesis, service quality has a partial and positive effect on customer satisfaction, Second, store atmosphere has a partial and positive effect on customer satisfaction, Third, location partially does not have a positive effect on customer satisfaction and location have a simultaneous effect on customer satisfaction at the Seblak Prasmanan Ndaa. Theoretical contribution/Originality : This research has a role in developing customer satisfaction theory and providing knowledge about factors and indicators that are important in influencing customer satisfaction. Practitionel/Policy implication: This research can provide insight to business actors so that they can maintain good service quality, maintain customer comfort through an organized store atmosphere, and a neat location so that customer satisfaction can remain the main priority as a regular customer. Research limitations: This research is limited only to the aspects of service quality, store atmosphere, and location on customer satisfaction during the 2024 ndaa buffet.